Fetal liver T2* values: Defining a standardized scale. Issue 6 (10th April 2013) - Goitein, Orly; Eshet, Yael; Hoffmann, Chen; Raviv‐Zilka, Lisa; Salem, Yishay; Hamdan, Ashraf; Goitein, David; Kushnir, Tamar; Eshed, Iris; Di‐Segni, Elio; Konen, Eli
Abstract : Purpose: To define the normal T2* values of liver in the third trimester of pregnancy in normal fetuses. Materials and Methods: Multi‐echo gradient echo T2* sequence was applied to the fetal abdomen in the axial plane in women undergoing a fetal MRI (1.5 Tesla [T], MRI system). A region of interest, best visualizing in the liver parenchyma was used for measurements. Studies were independently read by two experienced readers to assess intra‐ and interobserver variability. Results: The study cohort included 46 pregnant women undergoing fetal MRI for any indication other than liver pathology evaluation. Three scans were excluded due to fetal motion. Average maternal and gestational age were 33 ± 4 years and 31.9 ± 3 weeks, respectively. Average T2* values were found to be 19.7 ± 7.4 ms. The intra‐ and interobserver agreement were very good: 0.93 and 0.8–0.084, respectively. Conclusion: T2* MRI allows noninvasive evaluation liver iron content in the third trimester fetus. Measured values at this stage of pregnancy are significantly lower compared with values cited in the literature for adults. This is of major importance in the correct diagnosis of fetal iron overload states. We propose this as the standard reference when evaluating fetal iron overload pathology. J. Magn. Reson. Imaging 2013;38:1342–1345. © 2013 Wiley Periodicals, Inc.